2021
DOI: 10.1177/2050312121994358
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behavior and its associated factors among daily laborers in Arjo-Didessa sugar factory, Jimma Arjo, Southwest Ethiopia: An institution-based cross-sectional study

Abstract: Background: Ethiopia is one of the sub-Saharan African countries where the young population is densely found. Many studies reveal that the magnitude of risky sexual behavior is high in the youth. The consequences of risky sexual behavior developed during youth life may affect the sexual behavior in adult life, such as increasing the risk of acquiring and transmitting sexually transmitted infections, and predisposing to unwanted pregnancies. Our objective was to assess the risky sexual behaviors among daily lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…These findings are relevant to prior studies that reported that poverty and economic depravity, in particular, are the risk factors for RSB and premarital sexual practices among young people, especially girls (23,33). In agreement with previous studies conducted in SSA countries that indicated students living with their parents and experiencing domestic violence had a greater risk of being engaged in RSB than their counterparts (6,12,34), our study revealed that living without biological parents or experiencing domestic violence are associated with an increased prevalence of RSB. This was because the students who do not live with their genetic parents also do not get sexual and reproductive health education and easily experience a lack of coparenting and parental monitoring.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are relevant to prior studies that reported that poverty and economic depravity, in particular, are the risk factors for RSB and premarital sexual practices among young people, especially girls (23,33). In agreement with previous studies conducted in SSA countries that indicated students living with their parents and experiencing domestic violence had a greater risk of being engaged in RSB than their counterparts (6,12,34), our study revealed that living without biological parents or experiencing domestic violence are associated with an increased prevalence of RSB. This was because the students who do not live with their genetic parents also do not get sexual and reproductive health education and easily experience a lack of coparenting and parental monitoring.…”
Section: Discussionsupporting
confidence: 90%
“…Human immunodeficiency virus (HIV) infection continued to be a major public health problem in Ethiopia ( 1 , 2 ). The country was one of the fourth countries that reported the highest number of new HIV infected individuals in Africa ( 3 ), whereby 22,300 people were newly infected and 690,000 were living with HIV/ acquired immune deficiency syndrome (AIDS) at the end of 2018 ( 4 ). HIV/AIDS was responsible for an estimated 34% of all young adult death rates in Ethiopia, and 66.3% of all young adult deaths in urban Ethiopia between the ages of 15–49 ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ART decreases patients' viral loads to undetectable levels, leading to the false impression that they are no longer infectious ( 9 , 10 ). However, it is important to remember that risky sexual behavior puts people at risk for a range of sexual-related problems such as contracting STIs, unintended pregnancies, and septic abortions ( 3 , 4 , 8 ). Available studies reported that risky sexual practices expose PLWHA clients to new HIV strains resistant to antiretroviral therapy (ART) ( 5 , 11 ).…”
Section: Introductionmentioning
confidence: 99%